(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of the study was to analyze current findings of pioneering research on the development of auditory localization capacity in babies through the document review technique through four phases: Preparatory, descriptive, interpretive and synopsis. The findings show that the sound response threshold decreases with the age of the infant, the middle ear is still immature, as is the frequency discrimination. The discovery and encoding of new sound information takes only a few months in the infant and is affected by the maturation of the middle ear, however it loses relevant information that should be transmitted to the brain. The infant learns sight-sound associations after birth as well as expectations about these events in a three-dimensional reality because of their repetition.